Die Entwicklung von Gefangenenraten in Europa unter besonderer Berücksichtigung der Schweiz - Dünkel, Frieder (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Prison rates are often seen as a sign of how tough a country is on crime—but what do they really tell us about criminal justice and criminal policy? This article looks at the issue in a European comparison, with a special focus on Switzerland. It suggests that prison rates shouldn't be looked at on their own, but in relation to incarceration rates, average sentence lengths, and structural features of the prison population. At first glance, Switzerland appears moderate in comparison with other countries, but on closer inspection it exhibits some striking characteristics: a high proportion of short prison sentences, an above-average rate of pre-trial detention, and a high proportion of foreign nationals. These points point to potential for a more differentiated, human rights-based prison policy. The article thus provides an empirically sound basis for a new way of thinking about imprisonment in Switzerland. (machine translation)